Students' Algebraic Thinking Profile at Technology-Assisted Learning in Mathematics That Enhances Their Critical Thinking - Badawi, Ahmad; Billah, Farda Azkiya; Dewi , Nuriana Rachmani (Mandalika Mathematics and Educations Journal, 2025)
This study aims to examine the effectiveness of the Prepospec learning model, which is assisted by Google Sites, in enhancing students’ critical thinking skills and explores its impact on their algebraic thinking ability. The material learned in this study was the linear equation and its gradient. Mixed methods were used in this study. The quantitative method was used to determine the effectiveness of the Prepospec learning model assisted by Google Sites on students’ critical thinking skills, while the qualitative method was used to characterize their algebraic thinking ability. The results of this study indicate that integrating the Prepropspec model with digital platforms like Google Sites can serve as a promising and effective strategy in mathematics education to enhance students' critical thinking competencies more effectively than conventional Problem-Based Learning (PBL) approaches. Furthermore, based on the analysis, students who experienced the Prepospec learning model showed better performance in algebraic thinking ability. This is shown by their performance in each indicator of algebraic thinking ability.